Nietzsche, Philology, and Philosophy: Conjunctions on the Horizon of Criticism - Carrión Arias, Rafael (Logos. Anales del Seminario de Metafísica, 2020)
Nietzschean philosophy is a philological philosophy. Beneath the Nietzschean legacy of maturity prevails a critical-methodological basis discovered by him in his years of philological practice and from which a profoundly original philosophical gaze emerges. This article aims to show the reasons for this coincidence in a journey of continuity through the problem of critique.
Keywords: (philological) method; Kulturkritik; criticism; critique of ideology; text fetishism; hermeneutics